Relationship Between Knowledge Level And Severity Of Rheumatoid Arthritis Pain In The Elderly Posyandu Environment Of Tlogosari Kulon Community Health Center - Alfian Izzul Ramadhan; Nina Anggraeni Noviasari; Susilo Budi Pratama (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background:Rheumatoid arthritis is almost experienced by 70% of those over 50 years old which is characterized by structural damage to the joints. This disease is mostly located in the hands, wrists, and joints that support the body's weight such as the knees, hips, and back due to the continuous pressure process for years. Many people are not aware of a disease that occurs in them because often the symptoms that appear are not prominent and due to the lack of public knowledge.Objective:This study aims to determine the relationship between the level of knowledge and the severity of rheumatoid arthritis pain in the elderly health post environment of Tlogosari Kulon Health Center. Method:The method used is descriptive analytic with cross sectional design. Sampling using purposive sampling technique based on inclusion and exclusion criteria so that 27 elderly people were obtained. Data collection using the knowledge questionnaire to measure the level of knowledge of rheumatoid arthritis RAPS questionnaire to identify rheumatoid arthritis pain. Results: Respondents who have a good level of knowledge are 15 people (46.9%) and those who have sufficient knowledge are 17 people (53.1%). Respondents with low incidence of rheumatoid arthritis are 13 people (40.6%) and respondents with high incidence of rheumatoid arthritis are 19 people (59.4%). Based on the chi-square analysis, it is known that the significance is 0.036 <0.05. So it can be concluded that the level of knowledge of the elderly about rheumatoid arthritis has a relationship with the severity of rheumatoid arthritis pain.